The hidden foundation : cinema and the question of class - James, David E., 1945-; Berg, Rick (University of Minnesota Press, 1996)
Ranging from the earliest days of the cinema to the present, The Hidden Foundation reestablishes class as a fundamental aspect of film history. Featuring prominent film scholars and historians acting to inaugurate a new type of film studies, this volume is unique in its international scope, diversity of perspectives and methodologies, and the cultural, political, and historical sweep of its analysis.
Keywords: Motion pictures -- Political aspects.; Motion pictures -- Social aspects.; Social classes.; Social Class; Cinéma -- Aspect social.; Classes sociales.; Cinéma -- Aspect politique.; social classes.; PERFORMING ARTS -- Film & Video -- Reference.; PERFORMING ARTS -- Film & Video -- History & Criticism.; Motion pictures -- Political aspects; Motion pictures -- Social aspects; Social classes; Filmkunst.; Sociale aspecten.; Politieke aspecten.